A review of the genus Tycherobius (Acari: Camerobiidae), with descriptions of four new species from Australia - Fan, Qing-Hai; Walter, David E. (Zootaxa, 2006)
This is the first review on the genus Tycherobius Bolland since its establishment in 1986. We studied characters of the genus, provide distribution and habitat information, and described four new species from Australia: Tycherobius stipula sp. n., from grasstree litter in Brisbane and wetsandy heath litter in Cooloola, T. australis sp. n., from forest litter in Brisbane, wet-sandy heath litter in Cooloola, T. acicula sp. n., from litter in African Mahogany plantation in Far North Queensland and T. elongata sp. n., from forest litter in Brisbane. We also give a key to adults of the genus.